Field measurement of coefficient of friction in rails using a hand-pushed tribometer. (February 2015) - Areiza, Y.A.; Garcés, S.I.; Santa, J.F.; Vargas, G.; Toro, A.
Abstract: The coefficient of friction (COF) on the rail of a commercial railway was measured in the field using a hand-pushed tribometer. Two different friction modifiers (FM), a flange lubricant and water were manually applied on the top of the rail and creep curves were obtained for contact pressures of 1.0 and 1.2 GPa. The coefficient of friction was between 0.42 and 0.55 for dry tests, between 0.39 and 0.44 for water lubricated tests, and ranged from 0.13 to 0.22 when the FMs or flange lubricant were added. Thicker layers and greater contact pressures led to lower values of COF. In comparison to the dry condition, the effect of contact pressure was much less significant when an interfacial product was applied. Highlights: The COF at the wheel/rail interface was measured using hand-pushed tribometer. The effect of interfacial products and the contact pressure on COF is presented. A custom-made friction modifier was compared with a commercial product. The creep curves are shown for each condition of measurement.